hggggg666
27.04.2023 14:14
Алгебра
Есть ответ 👍

Разложите на множители квадратный трехчлен ​

188
284
Посмотреть ответы 2

Ответы на вопрос:

yayiliya
4,6(1 оценок)

a)   -x²+9x-8 = -x²+x+8x-8 = (-x²+x)+(8x-8) = -x(x-1) + 8(x-1) =

= (x-1)(-x+8) =(x-1)(8-x)

б) \frac{1}{3}x^{2}+x-6=\frac{1}{9}(3x^{2}+9x-54)=\frac{1}{9}(3x^{2}+18x-9x-54)=

=\frac{1}{9}((3x^{2}-9x)+(18x-54))=\frac{1}{9}(3x(x-3)+18(x-3))=\frac{1}{9}(x-3)(3x+18)=

=\frac{1}{9}*3(x-3)(x+6)=\frac{1}{3}(x-3)(x+6)

kornienko123456
4,6(84 оценок)

Вот и всё надеюсь всё понятно

Популярно: Алгебра